Transplantation of tissue‐engineered cell sheets for stricture prevention after endoscopic submucosal dissection of the oesophagus. Issue 6 (1st December 2016) - Jonas, Eduard; Sjöqvist, Sebastian; Elbe, Peter; Kanai, Nobuo; Enger, Jenny; Haas, Stephan L; Mohkles‐Barakat, Ammar; Okano, Teruo; Takagi, Ryo; Ohki, Takeshi; Yamamoto, Masakazu; Kondo, Makoto; et al.
Abstract : Background and objective: Endoscopic mucosal dissection (ESD) is a treatment option for oesophagus tumours localized to the mucosa enabling en bloc removal of large lesions. The resulting larger mucosal defects have resulted in an increase in the occurrence of post‐treatment strictures. Transplantation of autologous cell sheets, cultured from oral mucosa, has been shown to prevent post‐ESD strictures. The aim of the study was to assess the efficacy and safety of cell sheet transplantation after oesophageal ESD in a Western patient population where reflux‐associated pre‐malignant and malignant conditions predominate. Methods: Patients with Barrett's oesophagus associated high‐grade dysplasia or early adenocarcinoma where ESD entailed a resection >3 cm in length and ≥75% of the circumference were eligible for treatment under hospital exemption. Cell sheets were cultured from buccal mucosa according to Good Manufacturing Practice and were endoscopically applied to the post‐ESD defect directly after resection. Patients were followed with weekly endoscopy examinations, including confocal laser microscopy, for a total of four weeks. Results: Five patients were treated. ESD was extensive with resections being circumferential in three patients and 9–10 cm in length in two. The number of transplanted cell sheets ranged from two to six. Three patients developed strictures requiring two to five dilatation sessions. Conclusions: Cell sheet transplantation shows to be safe and feasible in a Western population. Results suggest that transplantation has a protective effect on the mucosal defect after ESD, decreasing both the risk for and extent of stricture formation.